The Use of Social Media on Tourist Decision Making in Determining Hotel Selection - Hubner, Ira B; Carina, Catrine; Ennelis, Ennelis; Natalia, Vitta; Juliana, Juliana (IJOSMAS, 2021)
Hotel is one of the important facilities to accommodate tourist while at the destination. Because of that, tourist needs various references to choose a hotel that fits the purpose. One of the references that can be used by tourists is social media which is a form of technological advances from the internet. Social media can provide the information needed by tourists both from hotel rates, location, facilities, description and reviews of the hotel. Therefore, this research is conducted to determine how the use of social media in the decision-making process of domestic tourists in choosing a hotel, and knowing the stages taken by tourists in determining hotel choices. This study uses a qualitative research approach with narrative/descriptive research methods. In collecting data, researchers use the interview method, structured and unstructured for more in-depth interviews with 20 people consisting of 2 social media expert, 2 hotel employees and 16 active social media users. Keywords: social media, hotel selection, tourist